In vitro and in vivo evaluation of a shape memory polymer foam‐over‐wire embolization device delivered in saccular aneurysm models. Issue 7 (31st July 2015) - Boyle, Anthony J.; Landsman, Todd L.; Wierzbicki, Mark A.; Nash, Landon D.; Hwang, Wonjun; Miller, Matthew W.; Tuzun, Egemen; Hasan, Sayyeda M.; Maitland, Duncan J.
Abstract: Current endovascular therapies for intracranial saccular aneurysms result in high recurrence rates due to poor tissue healing, coil compaction, and aneurysm growth. We propose treatment of saccular aneurysms using shape memory polymer (SMP) foam to improve clinical outcomes. SMP foam‐over‐wire (FOW) embolization devices were delivered to in vitro and in vivo porcine saccular aneurysm models to evaluate device efficacy, aneurysm occlusion, and acute clotting. FOW devices demonstrated effective delivery and stable implantation in vitro . In vivo porcine aneurysms were successfully occluded using FOW devices with theoretical volume occlusion values greater than 72% and rapid, stable thrombus formation. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1407–1415, 2016.